Progress on the mechanism of intestinal microbiota against colorectal cancer - Xing, Guoqiang; Cui, Yu; Guo, Zhiyue; Han, Bing; Zhao, Guogang (Frontiers in Cellular and Infection Microbiology, 2025)
The intestinal microbiota plays a crucial role in the occurrence and development of colorectal cancer, and its anti - colorectal cancer mechanism has become a research hotspot. This article comprehensively expounds on the molecular mechanisms of the intestinal microbiota in anti - colorectal cancer, including aspects such as immune regulation, activation of carcinogenic signaling pathways (it should be noted that it is more reasonable to be “inhibition of carcinogenic signaling pathways”), metabolite - mediated effects, and maintenance of intestinal barrier function. At the same time, it explores the roles and potential mechanisms of intervention methods such as probiotic supplementation therapy, immunotherapy, and fecal microbiota transplantation. In addition, it analyzes the impact of the intestinal flora on the therapeutic efficacy of colorectal cancer. The existing research results are summarized, and the future research directions are prospected, with the aim of providing new theoretical bases and treatment ideas for the prevention and treatment of colorectal cancer.